1976
DOI: 10.1111/j.1399-3054.1976.tb03939.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Nitrogen Supporting Growth and Embryogenesis in Cultured Wild Carrot Tissue

Abstract: This paper seeks to clarify conflicting reports on the nitrogen requirements for in vitro embryogenesis in Dauciis carota.Tissue derived from petiole explants of the wild strain of this species were tested with a variety of sources of cellular nitrogen under conditions otherwise favorable for in vitro embryogenesis. The use of very small, sieved and well-washed inocula reduced the carry-over of soluble materials with the inoculum. Embryo yield was quantified by direct counting of samples.Nitrate at concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0
2

Year Published

1981
1981
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(52 citation statements)
references
References 13 publications
3
47
0
2
Order By: Relevance
“…The differences were initially thought to be due to the higher sucrose concentration being used in MS medium than in B5, but this was not borne out by experimentation. Organogenesis in leafy spurge does not appear to be coupled closely to the nitrogen status of the culture: at least not to the extent reported for somatic embryogenesis in several other cell culture systems (Hyndman et al 1982, Kamada and Harada 1979, Masuda et al 1981, Thomas and Street 1972, Wetherell and Dougall 1976. Leafy spurge cells were capable of organogenesis in a wide range of reduced:oxidized nitrogen combinations, but the ratio used in MS medium (33:67) appears to be somewhat more favorable than others.…”
Section: Discussionmentioning
confidence: 83%
“…The differences were initially thought to be due to the higher sucrose concentration being used in MS medium than in B5, but this was not borne out by experimentation. Organogenesis in leafy spurge does not appear to be coupled closely to the nitrogen status of the culture: at least not to the extent reported for somatic embryogenesis in several other cell culture systems (Hyndman et al 1982, Kamada and Harada 1979, Masuda et al 1981, Thomas and Street 1972, Wetherell and Dougall 1976. Leafy spurge cells were capable of organogenesis in a wide range of reduced:oxidized nitrogen combinations, but the ratio used in MS medium (33:67) appears to be somewhat more favorable than others.…”
Section: Discussionmentioning
confidence: 83%
“…Somatic embryogenesis may be affected by different combinations of medium, such as minerals, sugar, vitamins and plant growth regulators (Wetherell and Dougall 1976, Kohlenbach 1978, Kamada and Harada 1979, Sharma et al 2005, Khaleda and Al-Forkan 2006. Amino acids are also found to enhance tissue culture, for example, Morcillo et al (1999) has reported glutamine and arginine play an important role of the maturation of oil palm somatic embryos (Morcillo et al 1999); Khaleda and Al-Forkan have reported that proline and casein hydrolysate stimulated callus induction and plant regeneration of five deepwater rice (Khaleda and Al-Forkan 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Wetherell & Dougall (1976), trabalhando com explantes oriundos de pecíolo de cenoura, observaram que ácido glutâmico e uréia poderiam individualmente e parcialmente substituir o cloreto de amô-nio como suplemento para o nitrato de potássio. Polacco (1976Polacco ( , 1977 verificou o crescimento de célu-las de soja em suspensão quando forneceu uréia ao meio, juntamente com adição de níquel.…”
Section: Introductionunclassified